Kepemimpinan dan birokrasi perpustakaan dalam perspektif Islam: Sebuah tinjauan teoritis untuk masa depan - Lailatur Rahmi; Johari Jamal (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2018)
Library is an organization whose existence cannot be separated from the influence of environmental changes, especially the rapid development of information technology. The human resources in it are very important elements to keep in mind, especially the figure of a leader. Leaders are an important foundation for the sustainability of an organization, so that the ultimate goal of an institution can be achieved well. In the study of Islam, leadership is a human nature according to the mandate of Allah Almighty for humans to be the vicegerent of Allah on earth. The leader becomes a very important figure and is closely related to the organization and organizational structure, structuring, bureaucracy and leadership concepts in an organization.